Functional Profile of CD8+ T-Cells in Response to HLA-A*02:01-Restricted Mutated Epitopes Derived from the Gag Protein of Circulating HIV-1 Strains from Medellín, Colombia - Sánchez-Martínez, Alexandra; Acevedo-Sáenz, Liliana; Alzate-Ángel, Juan Carlos; Álvarez, Cristian M.; Guzmán, Fanny; Roman, Tanya; Urcuqui-Inchima, Silvio; Cardona-Maya, Walter D.; Velilla, Paula Andrea (Frontiers in Immunology, 2022)
CD8+ T-cells play a crucial role in the control of HIV replication. HIV-specific CD8+ T-cell responses rapidly expand since the acute phase of the infection, and it has been observed that HIV controllers harbor CD8+ T-cells with potent anti-HIV capacity. The development of CD8+ T-cell-based vaccine against HIV-1 has focused on searching for immunodominant epitopes. However, the strong immune pressure of CD8+ T-cells causes the selection of viral variants with mutations in immunodominant epitopes. Since HIV-1 mutations are selected under the context of a specific HLA-I, the circulation of viral variants with these mutations is highly predictable based on the most prevalent HLA-I within a population. We previously demonstrated the adaptation of circulating strains of HIV-1 to the HLA-A*02 molecule by identifying mutations under positive selection located in GC9 and SL9 epitopes derived from the Gag protein. Also, we used an in silico prediction approach and evaluated whether the mutations found had a higher or lower affinity to the HLA-A*02. Although this strategy allowed predicting the interaction between mutated peptides and HLA-I, the functional response of CD8+ T-cells that these peptides induce is unknown. In the present work, peripheral blood mononuclear cells from 12 HIV-1+ HLA-A*02:01+ individuals were stimulated with the mutated and wild-type peptides derived from the GC9 and SL9 epitopes. The functional profile of CD8+ T-cells was evaluated using flow cytometry, and the frequency of subpopulations was determined according to their number of functions and the polyfunctionality index. The results suggest that the quality of the response (polyfunctionality) could be associated with the binding affinity of the peptide to the HLA molecule, and the functional profile of specific CD8+ T-cells to mutated epitopes in individuals under cART is maintained.